Android-Based Digital Dictionary of the Lani Tribe Language - Wiarton Liwiya; Melkior Sitokdana (APTIKOM SUMSEL, 2025)
Digital dictionaries are very useful tools in the process of learning and preserving language. This research aims to develop a digital dictionary based on the Lani Tribe language which can be accessed via the Android platform. Application development methods include user needs analysis, user interface design, application development, and user evaluation. This application development was carried out using the Java programming language and Android Studio technology. This digital dictionary provides word search features, word definitions, and examples of using words in sentences. The evaluation results show that this digital dictionary can be accessed easily and is useful for users who need a language reference for the Lani tribe. Overall, it is hoped that this digital dictionary can help in the preservation and development of the Lani language.